Stimulation of Anxiety Management for Instagram Followers @najwashihab by Comparing the Credibility of Quraish Shihab and Najwa Shihab - Nufindra, Ardin; Marta, Rustono Farady; Mulyadi, Fitri Sarasati; Engliana, Engliana; Ahmad, Rosmalia (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2023)
This research explores the reactions of Instagram followers @najwashihab after watching content featuring Najwa Shihab with Quraish Shihab on Najwa Shihab's YouTube channel. This research uses a quantitative approach with survey methods. Data was obtained from survey results among followers of the Instagram account @najwashihab regarding the credibility of Quraish Shihab and Najwa Shihab in conveying messages. The results of this research show that the communicants or audience, namely Instagram followers @najwashihab, show the influence that these two sources have on the management of anxiety. Exciting findings from this research show the reactions of communicants after seeing the messages delivered by Quraish Shihab and Najwa Shihab. Instagram followers @najwashihab can manage anxiety through mindfulness, namely being aware of their surroundings and being able to accept emotions openly. Further research should consider variables such as attitude, quality of life, mental health, self-love, quarter-life crisis, and anxiety management and consider questionnaires for comprehensive research.